The indentation thermal shock behavior of laminated ZrB2–SiC ceramics with strong interfaces. Issue 15 (15th November 2016) - Zhou, Peng; Fan, Youhua; Wang, Peng; Chen, Jing
Abstract: The thermal shock behavior of laminated ZrB2 –SiC ceramics with strong interfaces has been investigated by indentation-quench method through experiments and modeling, and was compared with that of a reference monolithic ZrB2 –SiC ceramic. The residual stress formed in the layers of laminated ZrB2 –SiC ceramics was also quantified by indentation technique. Results obtained by indentation-quench tests show that the monolithic and laminated ZrB2 –SiC ceramics present a similar crack growth behavior with increasing temperature difference. Nevertheless, the critical temperature difference, ΔTc, of laminated ZrB2 –SiC ceramics is much higher than that of the monolithic ZrB2 –SiC ceramic. A theoretical model considering all the stress intensity factors at the surface crack tip during thermal shock was established to analyze the mechanism of indentation thermal shock, which is in good agreement with the experimental results. What's more, theoretical results show that the contribution of residual surface compressive stresses in laminated ZrB2 –SiC ceramics to stress intensity make a negative contribution to the total stress intensity at the crack tips during thermal shock, which result in a better thermal shock resistance of laminated ceramics than monolithic ceramic.